2014
DOI: 10.1016/j.fuel.2014.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the regulated emissions, air toxics, ultrafine particles, and black carbon from SI-PFI and SI-DI vehicles operating on different ethanol and iso-butanol blends

Abstract: h i g h l i g h t s Emissions evaluation from ethanol and iso-butanol GDI and PFI vehicles. THC, CO, and NO x did not show strong trends with ethanol and blends. PM mass, number, and black carbon emissions were higher for the GDI vehicles. Increasing ethanol and butanol content reduced PM and number emissions. Butanol blends enhanced the formation of butyraldehyde emissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
64
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(79 citation statements)
references
References 45 publications
9
64
1
1
Order By: Relevance
“…A significant decrease in PM exhaust emission was measured for higher ethanol contents (>30 vol%) [24]. Karavalkis et al [25] and Lee et al [26] obtained similar results for fuels with low ethanol content. Here, blends with intermediate ethanol content (e.g.…”
Section: Introductionmentioning
confidence: 64%
“…A significant decrease in PM exhaust emission was measured for higher ethanol contents (>30 vol%) [24]. Karavalkis et al [25] and Lee et al [26] obtained similar results for fuels with low ethanol content. Here, blends with intermediate ethanol content (e.g.…”
Section: Introductionmentioning
confidence: 64%
“…The use of ethanol in engines have benefits in reducing life-cycle greenhouse gas emissions and harmful pollutant emissions [13]. It has been widely found that adding ethanol to PFI gasoline engines can suppress PM emissions [14,15]. However, for GDI engines, the results are divergent [16e19].…”
Section: Effects Of Ethanol On Pm Emissions In Gdi Enginesmentioning
confidence: 99%
“…However, under the same engine load, increases in ethylbenzene emission could be seen with ABE addition among ABE10, ABE20, and ABE30. Previous studies have found that the addition of ethanol or butanol in fuel blends could result in slightly higher ethylbenzene emission under low ethanol/butanol blend ratios [1,57]. ABE80 shows the lowest ethylbenzene emission, which is possibly due to the reduction of aromatics in the blend fuels.…”
Section: Benzene Toluene Ethylbenzene and Xylene (Btex) Emissionsmentioning
confidence: 86%
“…According to the results of previous studies [1,33,[45][46][47][48], acetaldehyde, 1,3-butadiene, benzene, toluene, ethylbenzene, and xylene isomers (o-xylene, m-xylene, and p-xylene) were selected as target toxic emissions from the exhaust gas. Because of the limitations in resolving the peaks in chromatography, the concentrations of m-xylene and p-xylene are shown as a total amount.…”
Section: Unregulated Emissionsmentioning
confidence: 99%
See 1 more Smart Citation